Konsep Teologi Kekudusan Seorang Hamba Tuhan Menurut John Chrysostom - Juliawati, Fransiska; Hendi, Hendi (Manna Rafflesia, 2021)
The holiness of a priest is an important review in this paper based on the study of the text in the book entitled Six Books on the Priesthood written by John Chrysostom. A book dealing with the priesthood. The holiness of life is not only seen from one aspect, but there are three things that must be considered both in the position as a representative of Christ, in shepherding, and spiritual growth through spiritual discipline. That is why an Imam has a very noble job despite many difficulties and temptations. Only the priest is qualified to bring offerings to God on a holy (intermediary) altar. The priest is not only responsible for his status as a representative of Christ (church confirmation) but must lead Christ's sheep to salvation even if his own life is at stake. Grace and mercy as well as an intimate relationship with God will further purify the heart, soul, and mind of a priest so that through the spiritual discipline he does (prayer and repentance) more and more reflect Christ in his life, including his pastorate.